2016
DOI: 10.4067/s0717-92002016000100018
|View full text |Cite
|
Sign up to set email alerts
|

Modelo empírico integral de una plantación de Eucalyptus granáis en Concordia, Entre Ríos

Abstract: Provincial 22 y vías del Ferrocarril, Concordia, Entre Ríos. SUMMARYThe Argentinian Mesopotamia is the core of fast-growing tree species plantations of the country. Eucalyptus grandis plantations constitute 90 % of the forested area with Eucalyptus spp. in NE Entre Rios. Based on previous studies on structural and functional features, a comprehensive model is here proposed on emergence of new properties linked to matter and ecosystem processes. Data from different plantations at harvest time were used: biomass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
3
0
3
Order By: Relevance
“…De acuerdo con Frangi et al (2016) y Santiago et al (2015, Eucalyptus grandis es de rápido crecimiento; por ello, los turnos forestales son cortos en comparación con otras especies destinadas al aserrío. A continuación, se presenta una breve comparación y la relación que guardan los cinco turnos considerados.…”
Section: Resultados Y Discusiónunclassified
“…De acuerdo con Frangi et al (2016) y Santiago et al (2015, Eucalyptus grandis es de rápido crecimiento; por ello, los turnos forestales son cortos en comparación con otras especies destinadas al aserrío. A continuación, se presenta una breve comparación y la relación que guardan los cinco turnos considerados.…”
Section: Resultados Y Discusiónunclassified
“…This study presents novel results in carbon stock considering all the components of a forest ecosystem and under conservation guidelines. Results were obtained in plantations of 14-17 year-old Eucalyptus grandis W.Hill ex Maiden, where it was found that these ecosystems accumulate on average 0.22 t C × km -2 in the aboveground biomass (Frangi et al, 2016). Furthermore, recently Sione et al (2018) have reported that the carbon stored in the aboveground tree biomass of native forests of the Spinal Phytogeographic province was 0.40 t C × km -2 , which represents a sequestration of 1.47 t CO 2 × km -2 .…”
Section: Carbon Stored In Aboveground Vegetationmentioning
confidence: 99%
“…There are several studies aimed to determine the carbon sequestration capacity in forest ecosystems. Various studies in Argentina showed the potential for carbon storage in forest biomass in various ecoregions (Davis et al, 2003;Gasparri & Manghi, 2004;Gasparri et al, 2008;Manrique et al, 2009;Peri et al, 2010Peri et al, , 2013Vega & Martiarena, 2010;Risio Allione, 2012;Manrique & Franco, 2012;Ontiveros et al, 2015;Barth et al, 2016;Frangi et al, 2016;Fernandez et al, 2018;Sione et al, 2018;Urdapilleta, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…El departamento de Concordia (Figura 1), lugar donde se llevó a cabo éste estudio, se caracteriza por concentrar más del 49 % de la producción forestal de la provincia (INTA, 2017). El clima en esta región es templado-cálido sin estación seca, con medias anuales de 18.7°C de temperatura y 1345.3 ± 287.7 mm de precipitación (Frangi et al, 2015). Los suelos predominantes son los correspondientes al orden Molisol, seguidos en cuanto a superficie ocupada por Vertisoles y Entisoles (USDA, 1999).…”
Section: Materiales Y Métodosunclassified
“…En Argentina, la superficie del territorio forestada con fines productivos se estima en 1.2 millones de hectáreas teniendo como principales especies de cultivo los géneros Pinus L., Eucalyptus L'Hér, Salix L. y Populus L. (MINAGRO, 2016). Es la región mesopotámica, ubicada al noreste del país e integrada por las provincias de Misiones, Corrientes y Entre Ríos la zona núcleo de las especies forestales de rápido crecimiento (Frangi et al, 2015), representando estas cerca del 80 % de las plantaciones forestales del país, con una total de 900 000 ha destinadas a esta actividad (IEA, 2016).…”
Section: Introductionunclassified